Identification of Elastic Orthotropic Material Parameters by the Singular Boundary Method (Advances in Applied Mathematics and Mechanics, 2018)
This article addresses the resolution of the inverse problem for the parameteridentification in orthotropic materials with a number of measurements merely onthe boundaries. The inverse problem is formulated as an optimization problem ofa residual functional which evaluates the differences between the experimental andpredicted displacements. The singular boundary method, an integration-free, mathematicallysimple and boundary-only meshless method, is employed to numericallydetermine the predicted displacements. The residual functional is minimized by theLevenberg-Marquardt method. Three numerical examples are carried out to illustratethe robustness, efficiency, and accuracy of the proposed scheme. In addition, differentlevels of noise are added into the boundary conditions to verify the stability of thepresent methodology.